P-BN13 How has the COVID pandemic affected outcomes in Elective Laparoscopic Cholecystectomy?An observational study in a UK Upper GI Surgical Unit. (16th December 2021) - Demetriou, George; Wanigasooriya, Kasun; Elmaradny, Ahmed; Al-Najjar, Ammar; Rauf, Mohammad; Martin-Jones, Alicia; Aboul-Enein, Mohamed Saad; Robinson, Steven J; Perry, Anthony; Wadley, Martin S; Mourad, Moustafa
Abstract: Background: COVID-19  has a significant impact on elective surgery for benign disease. When routine services resumed in April 2021, surgeons were faced with higher number of complicated cases. The aim of this study is to examine the effect of COVID-19 related delays on the outcomes of patients undergoing elective laparoscopic cholecystectomy (LC) in an upper gastrointestinal unit in the UK. Methods: Data were collected retrospectively on consecutive patients undergoing elective LC between 1/3/19 to 1/5/19 (Pre-COVID) and 1/4/21 to 11/6/21 (resumption of elective operating following COVID). The indications for surgery, intraoperative details, postoperative complications, length of stay (LoS) and 30- day readmission were compared between the two cohorts. We divided indications for surgery as inflammatory (acute cholecystitis, gallstone pancreatitis, CBD stone with cholangitis) vs non-inflammatory (biliary colic, gallbladder polyps, CBD stone without cholangitis). Data were analysed using the Mann-Whitney U-test and Chi-square or Fisher's exact test. A p value of < 0.05 was used for statistical significance.  Results: 159 patients were analysed,  106 in Pre-COVID vs 53 in Post-COVID. Both cohorts had similar age, gender, ASA-grade,  BMI. 68 (64.2%) of the pre-COVID cohort were operated for a non-inflammatory pathology compared to 19(35.8%) of the post-COVID cohort (p < 0.001). Less patients had total cholecystectomy (subtotal and failed surgery) in the post-COVID cohort [49(92.5%) vs 159 (100%) p = 0.01]. There was no difference in the operating time, conversion to open surgery, the need for drains, and no difference in the Clavien-Dindo grade complications. Two patients in pre- COVID cohort (1.8%) required re-operation for bile-leak and bowel injury and two in the post COVID cohort (3.7%) for bleeding and CBD-injury. There was no difference in day case discharge or 30-day readmission rate.  Conclusions: Surgery in the post-COVID cohort was associated with a higher incidence of inflammatory biliary disease, subtotal cholecystectomy and procedure abandoned.  Although the numbers in our study are small they highlight the need for enhanced preoperative assessment in elective biliary surgery as the NHS emerges from the acute phase of the pandemic.